Synthesis and Characterization of [Pt (5-acetylamino-1,10-phenanthroline)Cl2] - แสนสุข สุพจนี (Princess of Naradhiwas University Journal, 2019)
Synthesis and characterization of [Pt (5-acetylamino-1, 10-phenanthroline)Cl2] were studied, The reaction between bidentate ligand with Cis-[PtCl2(DMSO)2] were performed by using a reflux at 115 oC, for 25 hours and at the end of the reaction, the pale-yellow solid with 34% yield was obtained. It has been characterized by Elemental Analysis, High-Resolution Mass Spectrometry and 1H and 195Pt Nuclear Magnetic Resonance Spectroscopy.